Efeitos imediato e tardio da anestesia na função renal de cães submetidos a orquiectomia eletiva - Silva, Janine Giovanini da (2023)
In veterinary medicine, the literature on renal injury due to anesthesia is scarce due to the fact that follow-up in the immediate and even late postoperative period is often not performed, even if studies report that this is the time with the greatest risk of complications. Due to the scarcity of scientific material on this subject, renal injury becomes an important consequence, since even anesthetic procedures can favor this complication. The objective of this study was to evaluate dogs submitted to orchiectomy with different anesthetic protocols in order to diagnose immediate or delayed renal injury through diagnostic tests to evaluate renal function. Forty-five healthy male dogs, from five months to five years old, weighing 5 and 15 kilograms were selected and evaluated in the immediate (after 6 hours) and late (after three months) post-anesthetic period after elective orchiectomy. The animals were randomly allocated into three groups, which were control group (CG), dexmedetomidine group (DG) and acepromazine group (AG). For immediate evaluation, collections were performed at the end of the procedure (30 minutes), after 6 hours and 24 hours, with a return after 3 months for late evaluation collection. In the immediate renal evaluation there were no significant changes through the results of erythrogram, leukogram, biochemical examination and urinalysis, with only differences in the variable HR at stage 5 between the DG (dexmedetomidine) and CG (control) differing the median value between them. No significant changes were observed in the late evaluation, making evident the importance of the animal being healthy and monitored during the trans and postoperative period. It is concluded that there were no immediate and late changes regarding the effect of anesthesia in healthy dogs after undergoing elective orchiectomy using pre-anesthetic medication with vasodilator and vasoconstrictor drugs used.